Medical Malpractice in Childbirth Using the Water Birth Method - Tasya Einakrisda Sheiba Simatupang (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
Tort is a form of act against the law, whether conducted intentionally or due to negligence, which may cause damages to another person. This research uses the normative empirical research method, by applying the case study approach and by interviewing a gynecologist, which is then analyzed by the author using the qualitative method. Purusant to this research result, it can be understood that the labor process with the water birth method is not recommended in Indonesia and it has not been regulated, however, there are still quite a lot of mother-to-be who choose to use this labor method and are assisted by the medical personnel. Even so, within this case, a form of medical malpractice conducted by a doctor to his patient resulting in death of the patient’s baby has been found. From this research, it can be concluded that the regulation concerning the water birth labor method is crucial to be regulated within Indonesia to prevent future fatalities.The author suggests that the regulation to prohibit the water birth labor method shall be regulated in Indonesia in the near future and all the doctors as well as other medical personnel shall be even more cautious when assisting patients within a labor process.